The use of the reed (Phragmites australis) in wastewater treatment on constructed wetlands - Todorovics, Csilla; Garay, Tamás M.; Bratek, Zoltán (Acta Biologica Szegediensis, 2005)
The constructed wetland is a near-natural wastewater treatment technique, where reed (Phragmites australis) is an important component. The high rate of small residential settlements (less than 2000 population equivalent (PE) in Hungary suggests the consideration of cost-effective, locally operating wastewater treating methods. The present casework compares the conventional activated sludge treatment with the near-natural root-zone technology by means of the pollutant removal capacity of currently operating waste treatment plants. Examination of the water quality data shows that reed bed systems have a stable removal efficacy of organics of a similar rate to the conventional technologies, while in view of nutrients they have higher retention ability, so are beneficial against eutrophication.